A novel one-step flocculation method for recycling wasterolling oil. Issue 14 (17th July 2016) - Liu, Cheng; Cao, Leichang; Ma, Peng; Wang, Jieni; Rong, Shaofeng; Han, Sheng
ABSTRACT: Waste rolling oil is a highly emulsified black liquid that is difficult to degrade under natural state and has become a great environmental problem. In this research, we a dopted a novel method called one-step flocculation method to deal with waste oil, identify the best refining conditions to separate oil, and analyze the extracted solid. Using the one-step flocculation method, the recovered oil is almost similar to the fresh oil and, therefore, suitable for recycling usage. Solid separated from the waste oil contained significant amounts of mineral fines that could be used as raw material.